2001
DOI: 10.1007/pl00011353
|View full text |Cite
|
Sign up to set email alerts
|

Laser Doppler Flowmetry in Combined Needle Acupuncture and Moxibustion: A Pilot Study in Healthy Adults

Abstract: Laser Doppler flowmetry (LDF) (DRT 4/Moor Instruments Ltd, Devon, UK) was used in this pilot study for monitoring the effects of an invariable acupuncture pattern on microcirculation of the skin before, during, and after combined needle acupuncture and moxibustion in 12 healthy volunteers (mean age 35.2 +/- 4.4 years, range 26-41 years, four female and eight male). According to the standards of traditional Chinese medicine (TCM), this acupuncture pattern is assumed to be unspecific and non-therapeutic. Flux de… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2002
2002
2018
2018

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 21 publications
(2 citation statements)
references
References 18 publications
0
2
0
Order By: Relevance
“…The thermal stimulation from moxibustion increases microcirculation [31] and promotes metabolism [32] by altering blood flow rate and cell membrane permeability. The heat from moxibustion also stimulates immune cells in the skin tissues, leading to immunomodulatory effects [33].…”
Section: Discussionmentioning
confidence: 99%
“…The thermal stimulation from moxibustion increases microcirculation [31] and promotes metabolism [32] by altering blood flow rate and cell membrane permeability. The heat from moxibustion also stimulates immune cells in the skin tissues, leading to immunomodulatory effects [33].…”
Section: Discussionmentioning
confidence: 99%
“…This technique provides promise and opportunity to adapt the methodology in various fields of research for example in cerebral monitoring (stroke, injury … ), transplantation surgery (skin grafts, free flaps … ), vital organ monitoring (organ viability), tumor vascular research (angiogenesis) and peripheral vascular research (diabetes). Studies have shown that it is both highly sensitive and responsive to local blood perfusion and is also versatile and easy to use for continuous monitoring [1,2].…”
Section: Introductionmentioning
confidence: 99%